How Modern Science Came into the World Four Civilizations, One 17th-Century Breakthrough - Cohen, H. Floris (Amsterdam University Press, 2010)
Once upon a time 'The Scientific Revolution of the 17th century' was an innovative concept that inspired a stimulating narrative of how modern science came into the world. Half a century later, what we now know as 'the master narrative' serves rather as a strait-jacket - so often events and contexts just fail to fit in. No attempt has been made so far to replace the master narrative. H. Floris Cohen now comes up with precisely such a replacement. Key to his path-breaking analysis-cum-narrative is a vision of the Scientific Revolution as made up of six distinct yet narrowly interconnected, revolutionary transformations, each of some twenty-five to thirty years' duration. This vision enables him to explain how modern science could come about in Europe rather than in Greece, China, or the Islamic world. It also enables him to explain how half-way into the 17th century a vast crisis of legitimacy could arise and, in the end, be overcome. Building on his earlier The Scientific Revolution: A Historiographical Inquiry (1994), Cohen's new book connects the latest research results in highly innovative ways, breaking up all-too-deeply frozen patterns of thinking about the history of science.